SOCIALIZATION OF THE M-PASSPORT APPLICATION TO MINIMIZE DIFFICULTIES IN USING THE M-PASSPORT AT THE CLASS II IMMIGRATION OFFICE IN WONOSOBO - Priati Assiroj; Andyko Mahendra Putra; Ni Putu Ayu Yuniartika Dewi; Bella Mega Rahmaningtias; Ifatul Afifah (Polteknik Imigrasi, 2022)
This article discusses the challenges that users may face when using the M-Paspor application, which replaces the Online Passport Services (APAPO) application. In the evolving digital era, the M-Paspor application offers more complex features and functions, which can be a hurdle for individuals who are not familiar with technology or have limited understanding of the passport issuance process. The article also summarizes the community service activities conducted by the community service team from Politeknik Imigrasi in collaboration with the Class II Wonosobo Immigration Office to socialize the M-Paspor application. Through these activities, the team provides a better understanding of the application's usage and the electronic passport issuance process. The implementation methods include preparation, execution, and evaluation. The article emphasizes the importance of clear support and guidance in the development of the M-Paspor application to ensure accessibility and effectiveness for users who are less tech-savvy.